A city's desert : no apples in the Big Apple? (A) - Jones, Jamie, (SAGE Knowledge. Cases., 2017)
The New York City Department of Health and Mental Hygienes Physical Activity and Nutrition Program needed to come up with an innovative solution to the many health problems, such as obesity, diabetes, and heart disease that plagued residents of poorer areas in the city, while increasing economic opportunity for neighborhood residents. The result was the launching of Green Carts, a new mobile food vending initiative to support the introduction of healthier food options to residents of food deserts in New York City boroughs. The challenge was navigating the diverse landscape of players and engaging all of the relevant stakeholders to come up with a solution that was both feasible and sustainable. This case exemplifies the how partnership and strategic alliances can be used to have significant social impact. The beauty of this example is that it simultaneously addresses two large social issues: 1) access to healthy food options in urban food deserts and 2) creating self-employment opportunities for members of disadvantaged communities. This case also illustrates how the public sector can act as social innovators.